PEMIKIRAN KEAGAMAAN MUHAMMAD BASUNI IMRAN - Haris, Didik M Nur; Abd Rahim, Rahimin Affandi (Pascasarjana UIN ANTASARI Banjarmasin, 2017)
Basuni Muhammad Imran (1883-1976) was a Indonesian reformer who live in Sambas, West Kalimantan, it has brought this area to reach the peak of science and modernity. The main patterns of Muhammad Basuni Imran thought is traditionalism, inklusifism and flexible in medium but strong in thawabit. This study revealed substantial contributions of Muhammad Basuni Imran in Islamic legal thought especially in purposes in Islamic laws (maqasid shariâah) and Islamic politic (siyasah sharâiyyah), through the implementation of the concept tadarruj, Maslahah mursalah, al-Tahaluf al-Siyasi, and local wisdom of jurisprudence in adopting the opinion of the validity prayers Friday at least 40 people.